Thermal plasticity potentially mediates the interaction between host Chilo partellus Swinhoe (Lepidoptera: Crambidae) and endoparasitoid Cotesia flavipes Cameron (Hymenoptera: Braconidae) in rapidly changing environments - Mutamiswa, Reyard; Chidawanyika, Frank; Nyamukondiwa, Casper (Wiley, 2022)
BACKGROUND